Inovasi "Pojok ISPA" dalam Pencegahan Infeksi Saluran Pernapasan Akut Berbasis Rumah Tangga Pasca bencana Banjir - Riady, Nurul; Maifrizal; Masri; BEM (Jurnal Ragam Pengabdian, 2026)
Flood disasters leave dry mud residue that significantly increases household dust particle concentrations, triggering a surge in Acute Respiratory Infections (ARI). This community service program aimed to reduce ARI prevalence through the "Pojok ISPA" innovation in Gampong Rhieng Blang, Pidie Jaya District, Aceh. The program involved two partner groups: PKK housewives (Partner I) and the Tunas Rhieng Blang Youth Group (Partner II). Implementation followed five stages: socialization, training, technology application, mentoring and evaluation, and program sustainability. The main technology applied was SIPISPA (Dust Suction System for ARI Prevention), a portable air filtration device capable of reducing indoor dust particle concentrations by 40–50% within 30 minutes of operation. The results showed a 60% decrease in mild ARI complaints among 25 partner families, with 85% of Partner I members able to independently operate the device. Twenty youth cadres were trained as peer health educators with 100% demonstrating competency in ARI mitigation procedures.